2008
DOI: 10.21273/jashs.133.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Biochemistry of Flower Color in Stokes Aster

Abstract: Stokes aster [Stokesia laevis (J. Hill) Greene] is a herbaceous perennial endemic to the coastal plains of the southeastern United States. Anthocyanin and copigment aglycones from flowers were characterized using high-performance liquid chromatography. Blue, lavender, violet, and albescent flowers each contained the anthocyanidin petunidin, although albescent flowers contained a substantially smaller amount. Pale pink flowers were found to contain only cyanidin. Anthocyanins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Overview of the color characteristics of floral tissues, tannin content, origin, and percent homozygosity of faba bean inbred lines used in this study. is consistent with simple Mendelian genetics (Barb et al, 2008). A three-gene model was also proposed for the inheritance of flower color in Anagallis monelli (Freyre and Griesbach, 2004).…”
Section: Discussionsupporting
confidence: 68%
“…Overview of the color characteristics of floral tissues, tannin content, origin, and percent homozygosity of faba bean inbred lines used in this study. is consistent with simple Mendelian genetics (Barb et al, 2008). A three-gene model was also proposed for the inheritance of flower color in Anagallis monelli (Freyre and Griesbach, 2004).…”
Section: Discussionsupporting
confidence: 68%
“…In order to find the changes in antioxidant activity through maturation, a separate principal component analysis for each state was performed. It was demonstrated that in ripe stage the superoxide anion inhibition appears to be greatly associated to flavanones/flavanonols system (r = 0.99); two types of flavonoids that also act as vascular pigments contributing with the whitish colour of piñuela fruits [41]. For unripe fruit, the same superoxide anion inhibitory activity but with total phenols (r = 0.96) was observed.…”
Section: Antioxidant Capacitymentioning
confidence: 90%